Impact of Cd+2 substitutions on structural and mechanical properties of Co0.6Ni0.4-xCdxFe2O4 (0.00≤ x≤0.40) system - Kashid, P.; Mathad, S.N.; Shedam, Mahadev R. (Physics and Chemistry of Solid State, 2023)
This article presents the structural and mechanical properties of Co0,6Ni0,4-xCdxFe2O4spinel ferrite nanoparticles. The as prepared samples were characterized by thermo-gravimetric differential thermal analysis to examine their phase transition. TGA/DTA analysis confirmed the reaction is endothermic in nature and the process completion temperature around 714.24oC is good for annealing the prepared ferrite powder. X-ray diffraction pattern revealed, Co0,6Ni0,4-xCdxFe2O4 have been well crystallized to spinel crystal structure. The average crystallite size ranging from 14.52nm to 16.92nm. FTIR spectra showed, two significant absorption bands (ν1 and ν2) in between 400 cm−1and 600 cm−1confirmed the spinel structured ferrites. Morphological observations revealed, the grain size of prepared ferrites lies in the range 0.85 to 0.21 μm. Raman spectra peak positions of both tetrahedral and octahedral sublattice shifted towards higher energy position.